2017
DOI: 10.1002/pon.4382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oncologists in distress: Systematic review and meta‐analysis

Abstract: Objective: High mortality from cancer and rising patient numbers can trigger distress among oncologists because of a heavy and emotionally demanding workload. This systematic review and meta-analysis assesses the prevalence of high levels of distress among oncologists. Methods:The PRISMA protocol is registered at the PROSPERO international prospective register (Ref. 2015:CRD42015016325). We categorized data items according to the following distress factors: burnout, psychiatric morbidity, stress, depression, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 59 publications
4
40
0
8
Order By: Relevance
“…The levels of burnout are also congruent with research examining general oncology staff and those working in palliative care (Martins Pereira, Fonseca, & Sofia Carvalho, ; Trufelli et al, ). The pooled meta‐analysis prevalence rates of burnout in the EE subscale found in this review (32%) are identical to Medisauskaite and Kamau's () systematic review and meta‐analysis findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The levels of burnout are also congruent with research examining general oncology staff and those working in palliative care (Martins Pereira, Fonseca, & Sofia Carvalho, ; Trufelli et al, ). The pooled meta‐analysis prevalence rates of burnout in the EE subscale found in this review (32%) are identical to Medisauskaite and Kamau's () systematic review and meta‐analysis findings.…”
Section: Discussionsupporting
confidence: 83%
“…To the authors' knowledge, this is the first systematic literature review of oncology physicians to focus specifically on all three subscales of burnout as measured by the MBI and their associated factors. One review has explored this area, but concerning the prevalence of high EE scores only (Medisauskaite & Kamau, 2017).…”
Section: Burnout Health Care and Oncologymentioning
confidence: 99%
“…Low PA is 10% higher in nurses compared with oncologists, which may be because this same empathy and greater patient contact produces a negative effect when a patient dies, leading nurses to feel that their work is inadequate, and possibly even to contemplate their own death . Although cancer survival rates have significantly increased in the last years, cancer remains one of the biggest causes of premature adult death and one of the leading causes of death in the world (8.2 millions deaths in 2012) …”
Section: Discussionmentioning
confidence: 99%
“…National research exploring the prevalence of physician burnout found that approximately 46% of U.S. physicians experienced burnout at the time of the study [9]. Studies among oncologists suggest an overall burnout incidence of 32% assessed by the Maslach Burnout Inventory-Human Service Survey [11]. For different disciplines, a point prevalence of 25%-48% among medical oncologists [12][13][14][15][16], 20%-40% among radiation oncologists [10,17], and 28%-36% among surgical oncologists [8,18,19] is reported.…”
Section: Introductionmentioning
confidence: 99%